IMPARTING RELIGIUS CHARACTER EDUCATION IN ELEMENTARY SCHOOL – AGED CHILDREN THROUGH RELIGIOUS ACTIVITIES AT THE BAJIGUR HOUSE DESA KRAGAN KABUPATEN REMBANG - Nurul Afidatun Nisya’; Moh Kanzunnudin; Ika Ari Pratiwi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Religious character education embedded in elementary school-aged children in Desa Kragan was still found to be low, such as the low motivation of the children to recite the Al-Qur’an and the lack of children’s politeness. This research aimed to describe the impartment of religious character education as well as inhibiting and supporting factors in the impartment of religious character education in elementary school – aged children through religious activities in the Bajigur House, Desa Kragan, Kabupaten Rembang. The research was conducted in Desa Kragan, Kecamatan Kragan, Kabupaten Rembang. This research utilized descriptive qualitative method. The subjects of this study were elementary school – aged children ranged from 7 to 11 years old. Data were collected through observation, interviews, documentation, and field notes. Then, the data were analyzed through the following steps: data reduction, data display, and coclusions. Tthe validity of the data were examined by using triangulation. The results of this research confirmed that the religius character in elementary school – aged childern was imparted through religious activities in the Bajigur House, including the practice of the congregation fardhu prayer, BTA activites, and reciting sholawat and yasin. Meanwhile, the inhibiting factors found in this research were that students still needed guidance due to their various background. Other factors were the lack of supervision from teacher and perents due to the lack of awareness of the value of religious character, and the lack of enthusiasm for children in participating in these activities due to the social factors of students both at school and at home. At last, the supporting factors included getting support from parents and the surrouding community as well as adequate facilities.